(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Covid-19 has been the test of time for corporates to act responsibly toward the sustainable development goal of gender equality. The present research is conducted to understand the representation of gender equality in Indian corporates through their websites during the pandemic of the Covid-19 second wave using the Impression management technique. Impression management taxonomy has been applied to lead the content analysis of the 110 corporate websites from public and private sector companies for a period of six months. It is found that the corporates have been using more assertive techniques than defensive and the private sector has been active in comparison to the public sector in working towards gender equality initiatives. The situation of pandemic resulted in low business and struggle for existence still some companies tried to be gender- sensitive. In a focus group discussion with corporate representatives, it is found that Covid-19 was a difficult situation even for the corporates, but by posting womencentric stories and sharing their concerns, it was possible for an organisation to get a dedicated women workforce. Websites thus can work as a potent corporate communication tool whereby promoting gender equality, a company can be a morale booster for its employees and can gather positive public support.